Assessing the effect of verbal working memory load on visuo-spatial exogenous orienting. - Santangelo, V; Spence, C (2007)
The aim of this study was to assess whether or not loading verbal working memory (WM) affects the exogenous orienting of visuo-spatial attention. Visuo-spatial exogenous orienting was measured under low/high WM load conditions by means of an orthogonal spatial cuing paradigm. Participants had to discriminate the elevation (up versus down) of a visual target preceded by a peripheral spatially-nonpredictive visual cue presented on either the left or right. This elevation discrimination task was carried out in-between a verbal WM test, in which a sequence of six digits (to be remembered for report at the end of the trial) was presented either in numerically ascending or random order (i.e., low and high load conditions, respectively). Participants made significantly more recall errors in the high load than in the low load condition, demonstrating that the verbal WM load manipulation had been effective. However, WM load did not interact with visuo-spatial exogenous orienting (i.e., comparable cuing effects were reported in both load conditions). These results are consistent with the view that peripheral visual onsets automatically capture spatial attention, regardless any concurrent increase of verbal WM load.